2021
DOI: 10.3390/en14113000
|View full text |Cite
|
Sign up to set email alerts
|

Towards Engineered Hydrochars: Application of Artificial Neural Networks in the Hydrothermal Carbonization of Sewage Sludge

Abstract: Sewage sludge hydrochars (SSHs), which are produced by hydrothermal carbonization (HTC), offer a high calorific value to be applied as a biofuel. However, HTC is a complex processand the properties of the resulting product depend heavily on the process conditions and feedstock composition. In this work, we have applied artificial neural networks (ANNs) to contribute to the production of tailored SSHs for a specific application and with optimum properties. We collected data from the published literature coverin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 40 publications
0
1
0
Order By: Relevance
“…FE-SEM images of CWH showed an irregular but porous surface morphology (Figure 2a,b). Hydrochars are typically amorphous materials with a low degree of crystallinity [14,15]. Following the deposition of Fe 3 O 4 , it was observed that CWH's surface morphology was not affected, but only covered by Fe 3 O 4 particles (Figure 2c,d).…”
Section: Characterizationmentioning
confidence: 99%
“…FE-SEM images of CWH showed an irregular but porous surface morphology (Figure 2a,b). Hydrochars are typically amorphous materials with a low degree of crystallinity [14,15]. Following the deposition of Fe 3 O 4 , it was observed that CWH's surface morphology was not affected, but only covered by Fe 3 O 4 particles (Figure 2c,d).…”
Section: Characterizationmentioning
confidence: 99%
“…Sewage sludge valorization is an important element for CE implementation in the wastewater sector (Klavins et al, 2021). According to the latest publications (Kapetanakis et al, 2021;Knötig et al, 2021;Xiong et al, 2021), hydrochar produced from thickened sewage sludge shows satisfactory fuel properties in terms of higher heating value and reduced ash content.…”
Section: Hydrochar Yield Indicator For Hydrothermal Carbonization Of ...mentioning
confidence: 99%